2013
DOI: 10.1155/2013/302920
|View full text |Cite
|
Sign up to set email alerts
|

Maternal SNPs in the p53 Pathway: Risk Factors for Trisomy 21?

Abstract: Abstract. The p53 family and its regulatory pathway play an important role as regulators of developmental processes, limiting the propagation of aneuploid cells. Its dysfunction or imbalance can lead to pathological abnormalities in humans. The aim of this study was to evaluate the effect of maternal polymorphisms TP53 c.215G>C (P72R), TP73 4 c.-30G>A and 14 c.-20C>T, MDM2 c.14+309T>G (SNP309), MDM4 c.753+572C>T and USP7 c.2719-234G>A as risk factors for Down Syndrome (DS) birth. A case-control study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…TP53 rs1042522 G > C has also been associated with fetal trisomy 21. C allele and CC genotype are common in the mother with trisomy 21 offspring [ 5 , 19 ]. This finding was in line with the results in the younger subgroup of our study but contrary to those in the advanced maternal age group perhaps for the coeffect with other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TP53 rs1042522 G > C has also been associated with fetal trisomy 21. C allele and CC genotype are common in the mother with trisomy 21 offspring [ 5 , 19 ]. This finding was in line with the results in the younger subgroup of our study but contrary to those in the advanced maternal age group perhaps for the coeffect with other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, seldom study has analyzed the MDM2 rs2279744 T > G polymorphism and fetal aneuploidy. Previous studies have shown a close association of MDM2 rs2279744 T > G with the human polycystic ovarian syndrome and human reproduction [ 5 , 23 ]. Strikingly, MDM2 rs2279744 T > G polymorphism is the key element in maintaining the genomic stability of somatic cells [ 4 , 22 ], which was not revealed in female gametes and embryos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, conducted in the city of Rio de Janeiro (Rio de Janeiro State, Southeast region of Brazil), the SNP309 G frequency was 0.26, an intermediate value between those of Europeans and Africans (Hu et al, 2007b), with no significant difference between self-declared Caucasian and mixed-ethnic participants (0.27 and 0.26, respectively). Different variant allele frequencies were found in Natal (Rio Grande do Norte State, Brazilian Northeast region) (European-descendant: 0.35; African-mixed descendant: 0.48) (Meissner et al, 2007), and in Porto Alegre (Rio Grande do Sul State, Brazilian South region) (0.39) (Bouquet et al, 2013). Such differences could be explained by the high ethnic heterogeneity of Brazilian populations (Saloum et al, 2013).…”
Section: Discussionmentioning
confidence: 99%